INTEGRASI NILAI-NILAI ISLAM DALAM PENDIDIKAN KELUARGA: STRATEGI MEMBANGUN GENERASI BERAKHLAK MULIA - Dastur Fadli Dastur Fadli (lembaga Sepercenter, 2024)
Problems in family education include several major challenges, such as parents' lack of understanding of Islamic values and how to teach them to their children, the influence of modern environments and cultures that often conflict with Islamic values, such as individualism and materialism, and ineffective educational methods, where parents tend to focus on ritual aspects without understanding the essence of Islamic values. The purpose of this study is to describe and analyze the integration of Islamic values in family education and strategies for building a generation with noble character. This study uses library research. The data sources used in this study are books, scientific journal articles, and research reports relevant to the research topic. The results of the study show that: 1). The concepts and principles of Islamic values that can be effectively integrated into family education to shape a generation with noble character are that the values of monotheism, noble character (such as honesty and compassion), and social values (such as justice and mutual assistance) are the main concepts that must be integrated into family education. The principle of compassion-based education is also important to create a supportive environment. 2). Strategies to support the integration of Islamic values in family education in building a generation with noble character are that effective strategies include early worship habits, parental role models, the use of Islamic stories, and open dialogue between parents and children. 3). The challenges and obstacles families face in integrating Islamic values into their children's education are that the main challenges include parents' lack of understanding of Islamic values, the influence of the modern environment, parents' busy schedules, and ineffective educational methods